The impact of training on small and medium enterprises (SMEs) performance - Yahya, A.Z.; Othman, M.S.; Shamsuri, A.L.S. (2012)
This study attempts to analyze the factors that impact training in Small and Medium Enterprises (SMEs) based on three perspectives which are manager's, enterprise's and external characteristics. Then, relationship between training and performance is examined. The methods used are descriptive analysis, Pearson correlation, stepwise regression procedures and t-test. The data for the study were collected through mail questionnaires sent out to selected SMEs. Of the total number 500 questionnaires mailed to SMEs in Malaysia, 27.6 percent responded and completed the questionnaires. The empirical information resulted from analyzing the data obtained from the SMEs, suggests that manager's, enterprise's and external characteristics affect the demand for training, and training has a positive impact on SMEs performance.